2020
DOI: 10.1073/pnas.1914670117
|View full text |Cite
|
Sign up to set email alerts
|

Single-vesicle imaging reveals lipid-selective and stepwise membrane disruption by monomeric α-synuclein

Abstract: The interaction of the neuronal protein α-synuclein with lipid membranes appears crucial in the context of Parkinson’s disease, but the underlying mechanistic details, including the roles of different lipids in pathogenic protein aggregation and membrane disruption, remain elusive. Here, we used single-vesicle resolution fluorescence and label-free scattering microscopy to investigate the interaction kinetics of monomeric α-synuclein with surface-tethered vesicles composed of different negatively charged lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 66 publications
3
63
2
Order By: Relevance
“…The different consequences of α-Syn/membrane interactions depending on their lipid composition suggest their relevance for both physiological function, like vesicle binding, and dysfunction, like mitochondrial membrane disruption. In the study by Hannestad et al (2020) , an initial α-Syn monomer binding accompanied by a rapid clustering of additional monomers causing membrane leakage was suggested, which might be consistent with previous reports of membrane-bound α-Syn being able to seed the aggregation of the protein ( Lee et al, 2002 ; Grey et al, 2011 ). However, further studies are needed to better characterize membrane-bound α-Syn aggregate species not only by using model membranes but also when bound to membranes in vivo .…”
Section: Alpha-synuclein Interaction With the Mitochondrial Phospholisupporting
confidence: 87%
See 1 more Smart Citation
“…The different consequences of α-Syn/membrane interactions depending on their lipid composition suggest their relevance for both physiological function, like vesicle binding, and dysfunction, like mitochondrial membrane disruption. In the study by Hannestad et al (2020) , an initial α-Syn monomer binding accompanied by a rapid clustering of additional monomers causing membrane leakage was suggested, which might be consistent with previous reports of membrane-bound α-Syn being able to seed the aggregation of the protein ( Lee et al, 2002 ; Grey et al, 2011 ). However, further studies are needed to better characterize membrane-bound α-Syn aggregate species not only by using model membranes but also when bound to membranes in vivo .…”
Section: Alpha-synuclein Interaction With the Mitochondrial Phospholisupporting
confidence: 87%
“…Notably, the pore forming activity was higher in mitochondrial-like membranes with high CL content as compared to bilayers with a phospholipid composition reflecting synaptic vesicle membranes ( Ghio et al, 2019 ). In line with these data, α-Syn monomers showed a favorable interaction with phosphatidylglycerol vesicles over phosphatidylserine vesicles, including deeper insertion into phosphatidylglycerol membranes resulting in extensive membrane rupture ( Hannestad et al, 2020 ). While phosphatidylserine is found in synaptic vesicle membranes ( Lim and Wenk, 2009 ), phosphatidylglycerol is a precursor for CL synthesis ( Stanacev et al, 1967 ), and as such plays an important role in mitochondrial membranes.…”
Section: Alpha-synuclein Interaction With the Mitochondrial Phospholisupporting
confidence: 59%
“…Recently, Hannestad et al investigated the kinetics of monomeric α-syn interaction with different lipid vesicles under both fluorescence and light-scattering emission at the single-vesicle level. They found α-syn induces obvious step-wise structural changes and asymmetric membrane deformation of individual phosphatidylglycerol vesicles with a very low α-syn concentration 10 nM (∼100 proteins per vesicle) (Hannestad et al, 2020). The pore formation mechanism was not concluded to result in membrane leakage when α-syn binds to the vesicles.…”
Section: Sm Fluorescence Imaging (Smfi)mentioning
confidence: 99%
“…4 have been observed by different SM methods. For example, Hannestad et al (2020) found that α-syn induces a step-wise disruption and asymmetric membrane deformation of DOPG (1,2-Dioleoyl-sn-glycero-3-phosphoglycerol). Aβ aggregates cause the leakage of the vesicle bilayer and rapidly cross the vesicle (Widenbrant et al, 2006).…”
Section: Contributions To the Understanding Of Amyloid Toxicity In LImentioning
confidence: 99%
See 1 more Smart Citation